Genetic diversity analysis in post rainy sorghum landraces and identification of rabi adaptive traits specific genotypes - Patroti, Parashuram Dattu; Madhusudhana, Ragimasalawada; Rakshit, Sujay; Devaraja, Nitesh Shirur; Sharma, Kuldeep Kumar; Elangovan, Maruthamuthu; Samdur, Mohan Yadav; Limbore, Ashok Ramchandra (Journal of Cereal Research, 2021)
Assessment of genetic diversity among sorghum landraces is essential for their efficient utilization in plant breeding. In the present study, 203 sorghum landrace accessions were phenotyped for two rabi growing seasons of 2016-17 and 2017-18 in a Randomized Block Design with three replications. Among the traits investigated, plant height was found more variable followed by dry fodder yield per plant, panicle weight per plant and grain yield per plant. The highest PCV and GCV was shown by dry fodder yield per plant (41.36 and 35.22 %), panicle weight per plant (38.49 and 32.84 %), grain yield per plant (36.30 and 27.95) and panicle length (33.06 and 29.81), respectively. The PCA revealed three important principal components correlated with grain yield per plant, panicle length and plant height that accounted for 70.30% of the total variation. The maximum inter-cluster distance was observed between cluster IV and V. Cluster VII had the highest mean value for grain and fodder yield.Â